Neuromuscular Fatigue Following Isometric Contractions with Similar Torque Time Integral - Rozand, V.; Cattagni, T.; Theurel, J.; Martin, A.; Lepers, R. (International Journal of Sports Medicine, 2015)
Torque time integral (TTI) is the combination of intensity and duration of a contraction. The aim of this study was to compare neuromuscular alterations following different isometric sub-maximal contractions of the knee extensor muscles but with similar TTI. Sixteen participants performed 3 sustained contractions at different intensities (25%, 50%, and 75% of Maximal Voluntary Contraction (MVC) torque) with different durations (68.5±33.4 s, 35.1±16.8 s and 24.8±12.9 s, respectively) but similar TTI value. MVC torque, maximal voluntary activation level (VAL), M-wave characteristics and potentiated doublet amplitude were assessed before and immediately after the sustained contractions. EMG activity of the vastus lateralis (VL) and rectus femoris (RF) muscles was recorded during the sustained contractions. MVC torque reduction was similar in the 3 conditions after the exercise (−23.4±2.7%). VAL decreased significantly in a similar extent (−3.1±1.3%) after the 3 sustained contractions. Potentiated doublet amplitude was similarly reduced in the 3 conditions (−19.7±1.5%), but VL and RF M-wave amplitudes remained unchanged. EMG activity of VL and RF muscles increased in the same extent during the 3 contractions (VL: 54.5±40.4%; RF: 53.1±48.7%). These results suggest that central and peripheral alterations accounting for muscle fatigue are similar following isometric contractions with similar TTI. TTI should be considered in the exploration of muscle fatigue during sustained isometric contractions.
Keywords: isometric contraction; voluntary activation; EMG activity; percutaneous neurostimulation; knee extensor muscles